Economic Growth: Addressing the Nexus of Education, Unemployment, and Poverty, an Islamic Perspective - Ifa Azzahra Farhatannisa; Muhammad Ghafur Wibowo; Tawat Noipom (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
This research aims to analyze the effects of education, unemployment, and poverty on economic growth in West Java. This research used a quantitative technique. The research was conducted from 2018 to 2022. The data source used is secondary data acquired from the Central Statistics Agency (BPS) using panel data methods. This research included 27 cross-sectional analyses across 27 districts/cities in West Java over a period of 5 years. The total number of observations included 135 samples. This research used panel data regression methods. The results indicate that educational attainment and unemployment rates affect economic growth. The poverty variable has a little influence on economic development. The findings indicated that all independent variables concurrently influence the dependent variable.